Suitability of building envelope for fire prevention / Nurul Farhanah Abdullah - Abdullah, Nurul Farhanah (2018)
Nowadays, building envelope is widely used in Malaysia. The use of this finishes increases the aesthetic value of building exterior. There are three types of building envelope such as cladding, infill panel and curtain wall. It also comes in various type of materials and installation. However, the insulation of building envelope can contribute to fire incidents. Therefore, a study will be conducted on the building envelope with three objectives: to understand the behaviour of building envelope, to analyse fire occurrence in building with building envelope, and to propose fire prevention methods for building envelope. The case study will be conducted to gather information by using desk study. It is expected that the flammable material is the major factor for the cause of fire. This paper will provide conceptual framework to study the building envelope in relation to fire incidents. In conclusion, fire of buildings that are caused by the building envelope can be prevented by complying with the UBBL and Malaysian Standard.